Absolute Electron Ionization cross sections for Cytosine. (August 2015) - Rahman, M A; Krishnakumar, E
Synopsis: Absolute partial and total electron ionization cross sections for the DNA base Cytosine are measured using Relative Flow Technique (RFT) up to 500 eV.